2021
DOI: 10.3390/nano11040996
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Submicrometer-Sized Meloxicam Particles Using Femtosecond Laser Ablation in Gas and Liquid Environments

Abstract: In pharmaceutical development, more and more drugs are classified as poorly water-soluble or insoluble. Particle size reduction is a common way to fight this trend by improving dissolution rate, transport characteristics and bioavailability. Pulsed laser ablation is a ground-breaking technique of drug particle generation in the nano- and micrometer size range. Meloxicam, a commonly used nonsteroidal anti-inflammatory drug with poor water solubility, was chosen as the model drug. The pastille pressed meloxicam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
3
5
0
1
Order By: Relevance
“…Our present work focuses on the femtosecond pulsed laser ablation of pressed meloxicam pastilles in distilled water (pulsed laser ablation in liquid, PLAL) and in air (pulsed laser ablation, PLA). This study is an extension of our previous investigation 35 , and it complements our studies on nanosecond pulsed laser ablation of meloxicam in liquid 36,37 , in air 38 and ibuprofen in vacuum 39 . The aim was to investigate the ablation process with laser parameters (femtosecond pulses with kHz repetition rate) that are orders of magnitude different from those in our previous works, and to see how suitable it is for pharmaceutical applications.…”
Section: Introductionsupporting
confidence: 62%
“…Our present work focuses on the femtosecond pulsed laser ablation of pressed meloxicam pastilles in distilled water (pulsed laser ablation in liquid, PLAL) and in air (pulsed laser ablation, PLA). This study is an extension of our previous investigation 35 , and it complements our studies on nanosecond pulsed laser ablation of meloxicam in liquid 36,37 , in air 38 and ibuprofen in vacuum 39 . The aim was to investigate the ablation process with laser parameters (femtosecond pulses with kHz repetition rate) that are orders of magnitude different from those in our previous works, and to see how suitable it is for pharmaceutical applications.…”
Section: Introductionsupporting
confidence: 62%
“…The fluorescence of meloxicam powder in the CH─ stretching region (2700–3200 cm −1 ) is so high that it could not be used for imaging. However, lower CARS shift regions showed a good signal, and a characteristic CARS spectrum [ 22 ] was obtained between 1400 and 1800 cm −1 ( Figure A). Furthermore, in the CARS spectrum area, both PVP and PMVE–MA showed no clear Raman peaks, making imaging our MN formulation possible.…”
Section: Resultsmentioning
confidence: 99%
“…[ 21 ] As a nondestructive method, CARS microscopy facilitates real‐time in situ imaging, thereby proving indispensable for examining the crystal structure of pharmaceuticals like meloxicam encapsulated within MN patches. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that nanoparticles smaller than 100 nm are more likely to cross the BBB (Nance et al, 2022). Eszter et al reduced the particle size down to submicron scale (50 nm) by laser ablation strategy, and applied them to transnasal drug delivery (Nagy et al, 2021). Furthermore, Ajay et al reduced the particle size to 20-25 nm, and successfully carried three drugs for HIV-1 (Figure 1C) (Singh et al, 2020).…”
Section: Functional Unit For Neurobiological Research Central Nervous...mentioning
confidence: 99%